Adventure time comics. Volume 4 - Johnson, Phillip Kennedy, 1970-; Sandoval, Antonio, 1967-; Davison, Max G.; Claretti, Luca; Nitz, Jai; Jordan, Justin; Di Meo, Mattia; Van Lente, Fred; Syed, Anoosha; Enger, Marie; Ayoub, Jenna; Passmore, Ben; et al. (Kaboom!, a division of Boom Entertainment, Inc., 2018)
Collects short comics featuring the citizens of the Land of Ooo.